2013
DOI: 10.1097/dbp.0b013e318287cdfe
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Children with Disabilities on Parent Health-related Quality of Life and Family Functioning in Kelantan and Its Associated Factors

Abstract: Both parents/caregivers' characteristics and children's characteristics contributed to family impact in local setting. Results of this study emphasize the importance of the whole family involvement as the focus of services and supports by health care providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 21 publications
5
23
2
1
Order By: Relevance
“…Majority of the caregivers were the children's biological parents. Similar to most of the studies, a large number of the participants were mothers who are the primary caregiver of the children (Hsieh et al 2009;Hu et al 2011;Isa et al 2013). This also showed that it is often the mother who forms a vital link between the child and health care professionals rather than father.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Majority of the caregivers were the children's biological parents. Similar to most of the studies, a large number of the participants were mothers who are the primary caregiver of the children (Hsieh et al 2009;Hu et al 2011;Isa et al 2013). This also showed that it is often the mother who forms a vital link between the child and health care professionals rather than father.…”
Section: Discussionsupporting
confidence: 62%
“…Some other factors that were found to be associated with parental stress were marital status (Norizan & Shamsuddin 2010), parental coping strategies (Dabrowska & Pisula 2010;Norizan & Shamsuddin 2010;Walsh et al 2013), and types of diagnosis of the children (Dabrowska & Pisula 2010;Rezendes & Scarpa 2011;Shobana & Saravanan 2014). Local research demonstrated that divorced or widowed mothers had higher parenting stress and lower parental and family functioning compared to married mothers (Norizan & Shamsuddin 2010;Isa et al 2013). The literature also has shown that caregivers used a broad range of coping strategies and that there are indications that some strategies are more successful in some situations than in others.…”
Section: Introductionmentioning
confidence: 99%
“…Physical HRQL scores were calculated by averaging the 6 items of physical functioning and psychosocial HRQL scores were calculated by averaging the 14 items across emotional, social, and cognitive domains. The PedsQL FIM is well-validated and has been used in studies of parental HRQL in pediatric chronic pain (Jastrowski Mano, Khan, Ladwig, & Weisman, 2011), ADHD (Limbers, Ripperger-Suhler, Boutton, Ransom, & Varni, 2011), sickle cell (Panepinto, Hoffmann, & Pajewski, 2009), and disabled populations (Isa et al, 2013). The Cronbach alpha was .92 for the physical HRQL score and .94 for the psychological HRQL score.…”
Section: Methodsmentioning
confidence: 99%
“…Research on children with complex disabilities suggests that their families face added challenges often resulting in lower parental HRQL (Isa et al, 2013). Studies of children with non-progressive neurodevelopmental disorders (King, King, Rosenbaum, & Goffin, 1999) and ADHD (Harrison & Sofronoff, 2002) highlight child behavior problems as an important predictor of parent well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the Malaysian population, some studies have been conducted examining the impacts of caregiving children with spina bifida, Down syndrome, mental retardation and other types of disabilities on the parents and family. The researchers have adopted different wellestablished instruments from Western to measure these impacts, such as Parenting Stress Index [13], Parental Stress Scale [12], PedsQL Family Impact Module [8] and General Health Questionnaire [13,17]. A central issue that guides this study is that the different instruments will yield variability in findings and different estimates of the values of health outcomes.…”
Section: Introductionmentioning
confidence: 99%